2002
DOI: 10.1074/jbc.m207525200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Putative Phosphorylation Sites in the Targeting and Shuttling of the Aquaporin-2 Water Channel

Abstract: In renal collecting ducts, a vasopressin-induced cAMP increase results in the phosphorylation of aquaporin-2 (AQP2) water channels at Ser-256 and its redistribution from intracellular vesicles to the apical membrane. Hormones that activate protein kinase C (PKC) proteins counteract this process. To determine the role of the putative kinase sites in the trafficking and hormonal regulation of human AQP2, three putative casein kinase II (Ser-148, Ser-229, Thr-244), one PKC (Ser-231), and one protein kinase A (Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
194
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 218 publications
(209 citation statements)
references
References 52 publications
9
194
1
1
Order By: Relevance
“…As in other models AQP2-S256A, an AQP2 form lacking the PKA consensus motif and which thus mimics the constitutively unphosphorylated protein, does not translocate to the plasma membrane in response to FSK ( Figure 4A). 26,27 Cell surface biotinylation experiments confirmed that increased amounts of wild-type AQP2 but not of AQP2-S256A were inserted into the plasma membrane in response to cAMP elevation ( Figure 4B). Thus, in HEK293 cells ectopically expressed AQP2 is subject to regulation as it occurs in primary IMCD cells and in vivo.…”
Section: Camp Elevation Induces a Rapid Increase In Aqp2 Protein Abunmentioning
confidence: 71%
“…As in other models AQP2-S256A, an AQP2 form lacking the PKA consensus motif and which thus mimics the constitutively unphosphorylated protein, does not translocate to the plasma membrane in response to FSK ( Figure 4A). 26,27 Cell surface biotinylation experiments confirmed that increased amounts of wild-type AQP2 but not of AQP2-S256A were inserted into the plasma membrane in response to cAMP elevation ( Figure 4B). Thus, in HEK293 cells ectopically expressed AQP2 is subject to regulation as it occurs in primary IMCD cells and in vivo.…”
Section: Camp Elevation Induces a Rapid Increase In Aqp2 Protein Abunmentioning
confidence: 71%
“…Alternatively, Ca 2ϩ can stimulate phosphodiesterase activity in collecting ducts consistent with the presence of calcium-calmodulin-stimulated phosphodiesterase (36). A PKC-dependent AQP2 retrieval from apical membrane of principal cells has also been observed (56). Other studies suggest that calcium/PKC-coupled signaling not only inhibits water flow but also inhibits Na ϩ absorption and K ϩ secretion in the collecting ducts (26,46,59).…”
Section: Discussionmentioning
confidence: 81%
“…Decreased glucosuria may be linked to decreased washout of glucose by the concomitant decreased diuresis and effects on renal glucose transporters. Decreased diuresis may be linked to reversal of diabetes-induced activation of protein kinase C by highdose thiamine and benfotiamine [6] and consequent reversal of the inhibition of water re-uptake by aquaporins in renal collecting duct cells [21,22]. In any event, STZ diabetic rats with high-dose thiamine therapy consumed less food than control STZ diabetic rats whilst maintaining similar body weights.…”
Section: Discussionmentioning
confidence: 99%